Recombinant adeno-associated virus-mediated delivery of antisense angiotensin II receptor 1 gene attenuates hypertension development - Li Xu-guang; Yan Jiang-tao; Xu Xi-zheng; Wang Jia-ning; Cheng Li-ming; Wang Tao; Zuo Ping; Wang Dao-wen (Acta Pharmacologica Sinica; Vol 28, No 11 (November 2007): Acta Pharmacologica Sinica, 2016)
Aim: The renin-angiotensin system plays a crucial role in the development and establishment of hypertension, and the pharmacological blockade of the system results in a reduction in blood pressure. In the present study, we investigated whether the effects of a novel, double-stranded, recombinant adeno-associated virus vector (rAAV)-mediated antisense angiotensin II receptor 1 (AT1R) gene efficiently prevents the development of hypertension induced by a high-salt diet in adult, male Sprague-Dawley (SD) rats. Methods: A rAAV was prepared with a cassette containing a cytomegaloviruspromoter and partial cDNA (660 base pairs) for the AT1R inserted in the antisense direction (rAAV-AT1-AS). A single tail vein injection of the rAAV-AT1-AS or rAAV-GFP (green fluorescent protein, a reporter gene) was performed in adult, male SD rats. Two weeks after injection, the animals were fed a diet containing 8% NaCl, and the systolic blood pressure was measured weekly using the tail-cuff method for 12 weeks. Results: The high-salt diet induced a significant rise in systolic blood pressure in the rAAV-GFP-treated animals; however, the rAAV-AT1-AS treatment attenuated the rise in blood pressure (142.7±4.5 mmHg vs. 117±3.8 mmHg, P